Comparing Mortality Risk Predictive Ability of Different Scoring Systems in Cirrhotic Patients with Bacteremia - Chi-Chieh Hung; Yin-Chou Hsu; Kuo-Hsuan Lin (Emergency Medicine International)
Patients with liver cirrhosis and bacteremia have substantially higher risk of mortality and morbidity. Our study aimed to investigate scoring systems that can predict the mortality risk in patients with cirrhosis and bacteremia. A single-center, retrospective cohort study was performed among adult patients who visited the emergency department from January 2015 to December 2018. All patients diagnosed with liver cirrhosis and bacteremia were enrolled and divided into survivor and nonsurvivor groups for comparison based on their 30-day in-hospital mortality event. The Pitt bacteremia score (PBS), model for end-stage liver disease (MELD) score, Child–Pugh score, and quick sequential Organ Failure Assessment (qSOFA) score were calculated and compared using the area under the receiver operating characteristic (AUROC) curves. A total of 127 patients (survivor: 86; nonsurvivor: 41) were eligible for this study. Compared with the nonsurvivor group, patients in the survivor group had significantly lower MELD score (22 ± 7 vs. 29 ± 5, p<0.001), lower proportion of high qSOFA (score ≥ 2) (23.3% vs. 51.2%, p<0.01), and high PBS (score ≥ 4) (7.0% vs. 34.1%, p<0.001) category. There was also a significantly different distribution in Child–Pugh classification between the two groups p<0.01. The survivor group had significantly lower proportion of acute-on-chronic liver failure (27.9% vs. 68.3%, p<0.001) and fewer number of organ failures p<0.001. In comparison of the discriminative ability in mortality risk prediction, PBS (AUROC = 0.83, 95% CI = 0.75–0.90, p<0.001) and MELD scores (AUROC = 0.78, 95% CI = 0.70–0.86, p<0.001) revealed a better predictive ability than Child–Pugh (AUROC = 0.69, 95% CI = 0.59–0.70, p<0.01) and qSOFA scores (AUROC = 0.65, 95% CI = 0.54–0.75, p<0.01). PBS and MELD scores both demonstrated a superior ability of predicting mortality risk in cirrhotic patients with bacteremia.